The apple columnar gene candidate MdCoL and the AP2/ERF factor MdDREB2 positively regulate ABA biosynthesis by activating the expression of MdNCED6/9. (25th November 2020) - Sun, Xin; Wen, Cuiping; Xu, Jihua; Wang, Yihe; Zhu, Jun; Zhang, Yugang
Abstract: MdCoL, which encodes a putative 2OG-Fe(II) oxygenase, is a strong candidate gene for control of the columnar growth phenotype in apple. However, the mechanism by which MdCoL produces the columnar trait is unclear. Here, we show that MdCoL influences abscisic acid (ABA) biosynthesis through its interactions with the MdDREB2 transcription factor. Expression analyses and transgenic tobacco studies have confirmed that MdCoL is likely a candidate for control of the columnar phenotype. Furthermore, the ABA level in columnar apple trees is significantly higher than that in standard apple trees. A protein interaction experiment has showed that MdCoL interacts with MdDREB2. Transient expression and electrophoretic mobility shift assays have demonstrated that MdDREB2 binds directly to the DRE motif in the MdNCED6 and MdNCED9 ( MdNCED6/9 ) gene promoters, thereby activating the transcription of these ABA biosynthesis genes. In addition, a higher ABA content has been detected following co-overexpression of MdCoL –MdDREB2 when compared with the overexpression of MdCoL or MdDREB2 alone. Taken together, our results indicate that an interaction between MdCoL and MdDREB2 promotes the expression of MdNCED6/9 and increases ABA levels, a phenomenon that may underlie the columnar growth phenotype in apple.